Desain Penampang Krueng Pandrah Dengan Program HEC-RAS - Ichsan Syahputra; Cut Rahmawati; Lores Sudarta (Jurnal Teknik Sipil Unaya, 2019)
Krueng Pandrah River was analyzed by cross section of a trapezoid-shaped river. To determine the capacity of river cross section capacity, it is necessary to do hydraulic modeling. From the results of modeling using HEC-RAS 5.0.5 1-dimensional flow stated that the Krueng Pandrah River with a trapezoid-shaped river cross section width of the river is 10.00 m, depth of 6.00 m, slope of the talud 1V: 1.5H and safe from flooding. The construction used to repair cliffs and river channel is River Revetment which is made of stone structure with a weight of 650 - 800 Kg / Unit. River Revetment Height is planned to be 6.00 m from the river bed, slope 1H: 1.5V, width of 2.50m Revetment gaiters, and 1.30 m thick rock layer. To maintain the stability of the Revetment against the decline and scouring that might occur behind it, a Non Woven Geotextile layer was installed as wide as the surface of the stone layer along the Revetment. For handling, river management, river normalization and flood mitigation, the flood return period used in this analysis is Q5 years of 163.02 m3 / sec.